Current Issues in Turkish Economics: Problems and Policy Suggestions - (:unkn) unknown (Peter Lang AG, 2019)
The book covers a wide range of issues in Turkish economy and aims to discuss the problems, challenges and potential of Turkey in various sectors. The topics covered in the book include areas related to macroeconomics and monetary economics (inflation expectations, determinants and conduct of monetary policy), labor economics (earning differences, overeducation in labor markets), health economics (adult obesity), tourism economics (tourism response to disruptive events) and energy economics (solar energy systems). The book is written in a format so that general readers who are interested in the Turkish economy can easily read and have a deep understanding of the current economic issues in Turkey. In addition, the book is suitable for usage in the related courses as a textbook at the undergrauate and masters level in the fields of economics and business. © Peter Lang AG 2019.